Factors Affecting Obesity in Children: The Contextual Model - (:unkn) unknown (ISTANBUL UNIV-CERRAHAPASA, 2015)
Childhood obesity is one of the most important public health problems of the 21st century. Obesity has many negative physiological and psychological consequences for children. The aim of the current study is to investigate the reasons of childhood obesity in terms of the contextual model. In recent years, rapidly increasing obesity has been associated with environmental causes rather than genetic causes. Many environmental variables are defined on the basis of individuals, families and communities, which are acting on the child's weight status in the contextual model. Modifiable factors which affect children's weight, including excessive and wrong feeding, lack of physical activity, and a sedantary lifestyle are considered as the most important reasons of obesity and are central to the contextual model. These factors are associated with populational, demographic, and social characteristics including parenting practices and family characteristics as well as education systems. In the fight against obesity, health professionals should understand individual, familial, and populational factors that lead to obesity and should place emphasis on modifiable factors in order to achieve effective protection and weight management. Determination of modifiable enviromental factors that lead to childhood obesity can guide studies aimed at preventing obesity.
Keywords: Child; diet; obesity; physical activity; the contextual model; PHYSICAL-ACTIVITY; CHILDHOOD OBESITY; EATING BEHAVIORS; DIETARY-INTAKE; PREVENTION; ETHNICITY; PATTERNS; DISEASE; GENDER; FAMILY